Comparison Of Outcome Between Conventional And Video Laryngoscope In Predicted Difficult Intubation - Islam, Maj Muhammad Nazrul; Hossain, Md Miraj; Hossain, Md Aulad; Rahman, S M Mostafizur; Moinuddin, Md; Banik, Debasish; Akhtaruzzaman, AKM (Bangladesh Armed Forces Medical Journal, 2024)
Background: Endotracheal intubation is the mainstay of airway management in general anaesthesia. Failure to intubate the trachea, often known as difficult intubation, is always a possibility. To overcome difficult intubation, different methods of instrumental support were developed. Some authors. Methods: From March 2018 to September 2019, a comparative cross-sectional study was conducted at BSMMU, Dhaka in the department of anesthesia, analgesia, and intensive care medicine. A total of 60 patients with predicted difficult intubation who were scheduled for elective surgery under general anaesthesia with endotracheal intubation were selected for the study. Prediction of difficult intubation was assessed by modified Mallampati class III and IV or thyromental height. Results: Time taken from visualization of glottis for insertion of ETT was 12.8±2.3 sec in conventional laryngoscope which was significantly lower in video laryngoscope (15.0±3.6) (p =0.006). Time taken to visualize the glottis was 13.2±1.7 sec in conventional laryngoscope and 13.2±4.0 sec in video laryngoscope (p>0.05). Total time for tracheal intubation was 49.0±6.4 sec in conventional laryngoscope and 53.2±9.9 sec in video laryngoscope (p>0.05). Intubation with first attempt by video laryngoscope was (30/30; 100%) as compared with conventional laryngoscope (27/30; 90%) (p>0.05). Conclusion: It is evident from the study that intubation with video laryngoscope in comparison to conventional laryngoscope might provide better outcome in terms of ease of intubation and number of attempts during intubation for patients undergoing elective surgery under general anaesthesia. Bangladesh Armed Forces Med J Vol 56 No (1) June 2023, pp 7-13